PENGARUH TERAPI BIRTH BALL TERHADAP INTENSITAS NYERI PADA PERSALINAN DI KLINIK PRATAMA HANNA KASIH MEDAN 2020 - Elsa Situmorang; Deswita E.K.C Gulo; Herfan Feronika Bago; Nelfian Laia; Sri Swarti; Debora Paninsari (COLOSTRUM JURNAL KEBIDANAN, 2020)
Pain in childbirth is a physiological process caused by myometrial contractions with different intensities for each mother and is a signal to inform the mother that she has entered the labor process stage. Pain in childbirth has the highest degree of pain among other pain, so that many women are not ready to have children because they imagine the pain that will be presented at the time of labor later. The general objective of this study was to determine whether there was an effect of birth ball therapy on pain intensity in labor at the Pratama Hanna Kasih clinic, Medan 2020. Univariate and bivariate analysis using Wilcoxon test analysis. Bivariate analysis is used to see the effect of the independent variable (independent) on the dependent variable using the Wilxocon test analysis. Of the 30 respondent mothers who carried out the variable therapy pre-test birth ball who were very painful and 19 respondents had pain (63%), and a minority of respondents had little pain, 11 people (37%). And on the post-test respondents the least pain was increased by 22 respondents (73%), while the minority of pain was quite severe as many as 8 respondents (27%). A significant effect on the effect of birth ball therapy on labor pain where the p value is 0.00 <0.05. The results are expected to have an effect on birth therapy on labor pain. The results of the Wilcoxon test analysis with a degree of significance (?) = 0.05 and a P value of 0.00 were obtained (? <0.05) which can be seen from the value which means that Ho is rejected and Ha is accepted. The conclusion is that there is an effect of birth ball therapy on labor pain